Potential clinical impact of metagenomic next-generation sequencing of plasma for cervical spine injury with sepsis in intensive care unit: A retrospective study - Wan, Jian; Duan, Liwei; Chen, Qitong; Wang, Lv; Bai, Jinxia; Hu, Jingyun; Lu, Xinyuan; Zhang, Tao; Song, Wei; Yang, Degang; Shan, Yi; Yan, Zhu (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical spine injury (CSI) accounts for significant mortality in Intensive Care Unit (ICU), whereas sepsis remains one of the major causes of death in patients with CSI. However, there is no effective method to diagnose sepsis timely. The aim of this study is to investigate the effect of Metagenomic next-generation sequencing (mNGS) on the pathogen features and the prognostic prediction of CSI patients with sepsis. A total of 27 blood samples from 17 included patients were tested by mNGS. Data of mNGS were compared with conventional culture method. The Kaplan-Meier plots were used to visualize survival curves. A Cox proportional hazards model was used to identify independent prognostic factors for survival. mNGS detected a wide spectrum of pathogens in CSI patients with sepsis, including 129 bacterial species, 8 viral species, and 51 fungal species. mNGS indicated 85.2% positive results, while conventional culture method only showed 11.1% positive results in the blood samples. Further analyses revealed that mNGS had no prognostic effect on the septic CSI patients in ICU, whereas positive results of blood culture were closely correlated with an increased hazard ratio (HR) (HR 77.7067, 95%CI 2.860-2641.4595, P = 0.0155). Our results suggested that mNGS application may provide evidence for clinicians to use antibiotics when a CSI case is diagnosed with sepsis.